Analysis of the danger and risk of flooding in the middle section of the Ega river in Navarre - Hoffrén Mansoa, Raúl (Geographicalia, 2022)
River floods constitute one of the most important and widespread natural risks in the world. For this reason, its study and analysis represent a great opportunity for the prevention and protection of the territory. In this study, the danger and risk of flooding of Ega river has been evaluated for its middle section through Navarre (Spain). The hydrological behavior of the river system has been analyzed and the information elaborated by PGRI has been used to determine the effects on territory under different flooding scenarios. These data have been checked from flow rates and satellite imageries related to the flood event of Ega river on December 2021. Results obtained are intended to help reduce the risk of flooding in this sector.